2013
DOI: 10.1161/circheartfailure.113.000440
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of 1 Year of Alagebrium and Endurance Exercise Training in Healthy Older Individuals

Abstract: Background-Lifelong exercise training maintains a youthful compliance of the left ventricle (LV), whereas a year of exercise training started later in life fails to reverse LV stiffening, possibly because of accumulation of irreversible advanced glycation end products. Alagebrium breaks advanced glycation end product crosslinks and improves LV stiffness in aged animals. However, it is unclear whether a strategy of exercise combined with alagebrium would improve LV stiffness in sedentary older humans. Methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 40 publications
(55 reference statements)
5
50
0
1
Order By: Relevance
“…Our observations of MICT are consistent with previous studies, where moderate-intensity aerobic exercise appears not to affect systolic function in healthy older adults (Fujimoto et al 2013; Spina et al 1993). Further, a recent study has reported an 8% increase in ejection fraction in older adults following 12 weeks of HIIT on the treadmill, but this finding remains to be confirmed in a randomized controlled trial (Molmen et al 2012).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our observations of MICT are consistent with previous studies, where moderate-intensity aerobic exercise appears not to affect systolic function in healthy older adults (Fujimoto et al 2013; Spina et al 1993). Further, a recent study has reported an 8% increase in ejection fraction in older adults following 12 weeks of HIIT on the treadmill, but this finding remains to be confirmed in a randomized controlled trial (Molmen et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Studies in patients with heart failure or hypertension have demonstrated HIIT can also be more effective in inducing left ventricular remodeling and improving systolic and/or diastolic function (Molmen-Hansen et al 2012; Wisloff et al 2007). In agreement with previous randomized studies, left ventricular morphology and diastolic function remained unchanged in our exercise intervention (Fujimoto et al 2013; Haykowsky et al 2005). Whether the modest benefits of HIIT in our study is because cardiac systolic function is usually well preserved in aging (Fleg and Strait 2012) and we excluded subjects with any cardiovascular disease, or due to the duration of the exercise intervention itself, is not clear.…”
Section: Discussionsupporting
confidence: 92%
“…Fujimoto et al (2013) found that a year of exercise training started later in life failed to reverse LV stiffening, possibly because of accumulation of irreversible advanced glycation end products in older humans. But, other two studies reported that a 3-month physical activity intervention induced a significant reduction of AGEs in blood middle-age humans (Goon et al, 2009;Yoshikawa et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The AGE breaker alagebrium is the only drug studied in humans so far that directly targets structural components that contribute to progressive arterial stiffness. Despite promising initial results, however, alagebrium has not been studied in phase III trials, perhaps related to a number of negative results in other therapeutic areas [99][100][101][102][103]. A number of nutritional supplements such as flavonoids [104,105], isoflavone [106], omega-3 [106] and tetrahydrobiopterin [107,108] acting via an antioxidant effect and/or improvement of NO bioavailability have also been shown to improve arterial stiffness.…”
Section: Origins Of Arterial Stiffness and Nurture Versus Nature?mentioning
confidence: 99%